Applications and challenges of glucocorticoids for anti-neutrophil cytoplasmic antibody-associated vasculitis - Wen Kai-lian; Li Gui-sen; Wang Li (Linchuang shenzangbing zazhi)
Anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitis are a diverse group of systemic autoimmune disorders characterized by the presence of ANCA in sera, involving frequently kidney and lung. Its etiology and pathogenesis are not fully elucidated. Although existing treatment with glucocorticoids plus immunosuppressant has greatly improved the prognosis, it is prone to relapse after remission and often accompanied by serious adverse events. Basic treatment of glucocorticoids lacks uniformity and standardization in its applications and it is a major factor of treatment-related adverse events. This review summarized the applications of glucocorticoids for ANCA-associated vasculitis to provide references for clinical practices.